Architecture modeling of satellite Internet simulation platform based on MBSE - LI Hongguang; LIU Yaoqi; ZHOU Yiqing; SHI Jinglin (Dianxin kexue)
The traditional text based system engineering method has some problems in the development of high complexity satellite Internet simulation platform, such as poor system design coordination and insufficient early simulation verification. The model-based systems engineering (MBSE) method was proposed to model the architecture of satellite Internet simulation platform. Firstly, a DV-MBSE and an integration verification architecture with external software were proposed. Secondly, based on MBSE methodology, the requirements analysis, functional decomposition and interaction structure modeling of the top architecture of the satellite Internet simulation platform were carried out. Finally, the validity of the model was verified by running logic verification and external model integration verification, thus supporting the design of satellite Internet.